Case report: Immune remission from generalized myasthenia gravis in a dog with a thymoma and cholangiocellular carcinoma - Mignan, Thomas; White, Robert; Stee, Kimberley; Bonanno, Giuseppe; Targett, Mike; Lowrie, Mark (Frontiers in Veterinary Science, 2023)
A 9-year-old male neutered Cockapoo was presented with an acute and progressive history of exercise induced weakness involving all limbs, and bilateral decreased ability to blink. Investigations revealed generalized myasthenia gravis alongside the presence of a thymoma and a cholangiocellular carcinoma. Symptomatic treatment through pyridostigmine bromide was used to control clinical signs, and complete surgical removal of the thymoma and cholangiocellular carcinoma was performed. Serum acetylcholine receptor antibody concentration was measured serially. Clinical remission defined as resolution of clinical signs alongside discontinuation of treatment was achieved by day 251 (8.2 months). Immune remission defined as normalization of serum acetylcholine receptor antibody concentration alongside resolution of clinical signs and discontinuation of treatment was achieved by day 566 (18.5 months). Neurological examination was normal, and the owners did not report any clinical deterioration during the final follow-up appointment on day 752 (24 months), hence outcome was considered excellent. This is the first report describing the temporal evolution of serum acetylcholine receptor antibody concentration in a dog with thymoma-associated myasthenia gravis which achieved immune remission following thymectomy. Treatment was successfully discontinued without any evidence of clinical deterioration thereafter despite serum acetylcholine receptor antibody concentration not normalizing for another 315 days (10 months).